2020
DOI: 10.1186/s12886-020-01574-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the therapeutic effects of surgery following prism adaptation test versus surgery alone in acute acquired comitant esotropia

Abstract: Background To compare the therapeutic effects of surgery following prism adaptation test versus surgery alone in acute acquired comitant esotropia (AACE). Methods A total of 46 patients with AACE were enrolled in this retrospective study. Among them, 26 patients underwent surgery following prism adaptation test (combination group) and 20 patients underwent surgery alone (surgery group). The following parameters were evaluated including success rate, distant and near dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In 2020, Zhang et al reported comparative results for the therapeutic effects of surgery following prism treatment versus surgery alone in cases of AACE. 19 Among the 46 cases, 26 underwent additional prism treatment before surgery (S+P group), and the remaining 20 cases were treated with surgery alone (S group), as in our report. Although no significant differences in motor success (≤10Δ) rate were observed between approaches at 12 months post-treatment (96% vs 90%, p > 0.05), the number of cases showing central near stereoacuity (≤60) "was significantly higher in the S +P group (85%) than in the S group (55%) at 12 months post-treatment.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…In 2020, Zhang et al reported comparative results for the therapeutic effects of surgery following prism treatment versus surgery alone in cases of AACE. 19 Among the 46 cases, 26 underwent additional prism treatment before surgery (S+P group), and the remaining 20 cases were treated with surgery alone (S group), as in our report. Although no significant differences in motor success (≤10Δ) rate were observed between approaches at 12 months post-treatment (96% vs 90%, p > 0.05), the number of cases showing central near stereoacuity (≤60) "was significantly higher in the S +P group (85%) than in the S group (55%) at 12 months post-treatment.…”
mentioning
confidence: 56%
“…18 Zhang et al also reported the results of therapeutic effects in 46 cases of AACE treated using surgery with preoperative prism treatment or surgery alone (Burian-Franceschetti type, n = 21; Bielschowsky type, n = 25). 19 They also recommended surgery following preoperative prism treatment based on the findings of improved binocular function and reduced recurrence rate. However, few studies have examined the benefits of prism adaptation test or preoperative prism treatment for AACE related to the excessive use of DDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When and how long a PAT is performed preoperatively differs from surgeon to surgeon and country to country [ 1 ]. Only recently, Zhang et al[ 18 ] compared the therapeutic effects of surgery following prism adaptation test versus surgery alone in Acute acquired comitant esotropia (AACE). They found no significant difference in success rate between the “prism plus surgery” group and “surgery” group 12 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with Ela-Dalman et al (2006) who et al 2018). Zhang et al (2020) showed that surgery following PAT with a duration of 1 week to 3 months in participants with AACE (acute acquired comitant esotropia) leads to improved binocular function and reduced recurrence rate (Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 99%